EFFECT OF LEVELS OF IRRIGATION AND NITROGEN ON BARLEY UNDER SALINE-SODIC CONDITION IN CENTRAL UTTAR PRADESH - Bhan, Suraj; Khokhar, R.P.; Agrawal, S.K. (Journal of Soil and Water Conservation, 2022)
With a view to find out optimum irrigation schedule and dose of nitrogen for barley on newly reclaimed saline sodic soils of Central Uttar Pradesh, a field experiment was conducted for three consecutive years from 1978- 79 to 1980-81, at the University Research Farm, Dalipnagar (Kanpur). The study revealed maximum yield of barley with 7 irrigations in two out of three years, however; in one year yield with 5 irrigations was at par with 7 irrigations. As regards the dose of nitrogen 60 kg N/ha yielded maximum (15.2 q/ha). The yield was slightly depressed when the dose increased to 90 kg N/ha.